Resúmenes de novedades - Foro Internacional, Revista (El Colegio de México A.C., 2025)
ALBERTO CASAS BENÍTEZ y MAURICIO I. DUSSAUGE LAGUNA (eds.). 2025. Debates emergentes sobre administración y políticas públicas. México: Flacso, 403 pp. KATHERINE KRIMMEL. 2025. Divergent Democracy. How Policy Positions Came to Dominate Party Competition. Princeton, NJ: Princeton University Press, 296 pp. LARS-ERIK CEDERMAN, LUC GIRARDIN, CARL MÜLLER-CREPON y YANNICK I. PENGL. 2025. Nationalism and the Transformation of the State Border Change and Political Violence in the Modern World. Reino Unido: Cambridge University Press, 394 pp. JULIA KRISTEVA. 2025. Nations Without Nationalism. Nueva York: Columbia University Press, 108 pp. SUZANNE METTLER Y TREVOR E. BROWN. 2025. Rural Versus Urban: The Growing Divide That Threatens Democracy. Princeton: Princeton University Press, 328 pp. BENJAMIN WILSON. 2025. Strange Stability. How Cold War Scientists Set Out to Control the Arms Race and Ended Up Serving the Military-Industrial Complex. Cambridge, MA.: Harvard University Press, 288 pp. MATTHEW FLINDERS, GERGANA DIMOVA, MARKUS HINTERLEITNER y R. KENT WEAVER (eds.). 2024. The Politics and Governance of Blame. Reino Unido: Oxford University Press, 800 pp. HUI ZHANG. 2025. The Untold Story of China's Nuclear Weapon Development and Testing. A Technical History. Boston, MA.: MIT Press, 352 pp. DARIO BATTISTELLA, JÉRÉMIE CORNUT y ELIE BARANETS, eds. 2026 (7ma. ed. actualizada). Théories des relations internationales. París: Presses de Sciences Po.